Between Piety And Lifestyle: Hijab Shar’i on the Commodification Practices of the Islamic Culture Industry - Abdul Rahim (Ulumuna, 2022)
The shar’i hijab has become a global fashion product targeting Muslim women. Nowadays, it is part of the cultural industry captured by capitalism in pursuit of profit. The shar’i hijab that displays a visualization of the discourse of piety and beauty makes consumption practices an effort to articulate the identity of Muslim women for religious observance. Massive distribution through the media or fashion show events is part of the visualization of the lifestyle of fashion fans which is echoed by the perpetuation of capitalism in the circulation of production, distribution, and consumption of hijab products which is reflected through the discourse of covering the genitals according to shar’i. Consumption of hijab product brands shows social class to differentiate themselves. This often leads to aesthetic violence in an effort to match the tastes of the lower class to force them to buy hijab products with the same brand as the figure they idolize. Consumption practices that show the articulation of Muslim women's identities in religious discourse are increasingly being captured by capitalism to create changes in hijab modes. The concept of obsolescence planning is part of production management for hijab product offerings that continue to grow, and capitalism is increasingly hidden behind the discourse of piety.